1994
DOI: 10.1038/bjc.1994.220
|View full text |Cite
|
Sign up to set email alerts
|

Expression of epidermal growth factor receptor in bladder cancer as related to established prognostic factors, oncoprotein (c-erbB-2, p53) expression and long-term prognosis

Abstract: Summary The expression of epidermal growth factor receptor (EGFR) was studied immunohistochemically in 234 cases of transitional cell bladder cancer. EGFR was overexpressed in 35% of cases and distinct nuclear localisation of EGFR positivity was found in 31% of the tumours. Overexpression was related to invasive growth, grade 2-3 histology, non-papillary type, DNA aneuploidy and high proliferation rate of cancer cells. The expressions of p53 and EGFR were interrelated, while expression of c-erbB-2 was independ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
106
3
7

Year Published

1996
1996
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 221 publications
(122 citation statements)
references
References 36 publications
4
106
3
7
Order By: Relevance
“…Nuclear expression of EGFR was further detected in other cell types and tissues, such as placentas, thyroids and immortalized epithelial cells of ovary and kidney origins (Cao et al, 1995;Lin et al, 2001;Marti et al, 2001;Lo et al, 2005a). High levels of EGFR was also found in the nuclei of many tumours, including those of skin, breast, bladder, cervix, adrenocorticord, thyroid and oral cavity (Kamio et al, 1990;Lipponen and Eskelinen, 1994;Lin et al, 2001;Marti et al, 2001;Lo et al, 2005a, c;Psyrri et al, 2005). In addition, EGFR has been shown to localize in the inner nuclear membrane (Cao et al, 1995;Klein et al, 2004).…”
Section: Detection Of Nuclear Egfrmentioning
confidence: 97%
“…Nuclear expression of EGFR was further detected in other cell types and tissues, such as placentas, thyroids and immortalized epithelial cells of ovary and kidney origins (Cao et al, 1995;Lin et al, 2001;Marti et al, 2001;Lo et al, 2005a). High levels of EGFR was also found in the nuclei of many tumours, including those of skin, breast, bladder, cervix, adrenocorticord, thyroid and oral cavity (Kamio et al, 1990;Lipponen and Eskelinen, 1994;Lin et al, 2001;Marti et al, 2001;Lo et al, 2005a, c;Psyrri et al, 2005). In addition, EGFR has been shown to localize in the inner nuclear membrane (Cao et al, 1995;Klein et al, 2004).…”
Section: Detection Of Nuclear Egfrmentioning
confidence: 97%
“…For instance, initial studies found EGFR in the nuclei of cells from various tissues, including thyroid cells, immortalized renal and ovarian epithelial cells, and primary tumors of the bladder and thyroid. 38,39 In subsequent reports, nuclear EGFR, but not cytoplasmic EGFR, positively correlated with tumor size and lymph node metastasis and negatively correlated with survival in breast cancer. 23 A microarray study demonstrated that several genes, including COX2, were activated by EGFR, but not by nuclear localizationedefective EGFR.…”
mentioning
confidence: 92%
“…The elevation of serum levels of either MMP2 or MMP3, or both, were also shown to be possible predictors of recurrence in patients with advanced urothelial carcinoma after resection (Gohji et al, 1996b). In contrast Grignon et al (1996) suggests that there is a strong correlation between high levels of TIMP2 immunostaining and poor outcome in patients with invasive bladder cancer.Growth factors and their receptors are important in tumour development and progression and several studies have shown that the presence of epidermal growth factor receptor (EGFR) in bladder cancer is associated with high tumour stage and grade and is a strong independent predictor of tumour progression and poor long-term survival (Lipponen and Eskelinen, 1994;Mellon et al, 1995). Levels of epidermal growth factor (EGF) are known to be high in urine with a mean value of 80 ng ml-' (Fisher and 215 …”
mentioning
confidence: 99%
“…Growth factors and their receptors are important in tumour development and progression and several studies have shown that the presence of epidermal growth factor receptor (EGFR) in bladder cancer is associated with high tumour stage and grade and is a strong independent predictor of tumour progression and poor long-term survival (Lipponen and Eskelinen, 1994;Mellon et al, 1995). Levels of epidermal growth factor (EGF) are known to be high in urine with a mean value of 80 ng ml-' (Fisher and Lakshmanan, 1990), but are lower in patients with bladder tumours and rise again after surgery (Fuse et al, 1992).…”
mentioning
confidence: 99%